STRATEGI PENGEMBANGAN KOMPETENSI GURU SEKOLAH DASAR - Fredy Fredy; Wa Ode Siti Hamsinah Day (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
The mandate of the law provides instructions teachers have four competencies, including pedagogic, personal, social, and professional. In its implementation, there are still many obstacles by teachers. Lack of skills in applying curriculum 2013, understanding the characteristics of students, knowledge of learning materials, the use of various and innovative learning models and methods, and the use of ICT in learning are obstacles by teachers. This study aims to the strategy of teacher competency development. A qualitative and descriptive approach became the method of this research, using the subject of an elementary school teacher in Bombana district. Data obtained from questionnaires and interviews were analyzed using the IFAS matrix analysis (internal factors analysis summary), EFAS (external factors analysis summary), and SWOT (strengths, weaknesses, opportunities, and threats). The results research an overview of the strategies implemented using the turnaround strategy, taking advantage of existing opportunities to overcome the weaknesses of the teachers for social, professional, and pedagogic competencies. The strategy for personal competence with an aggressive strategy is to use the strengths possessed by the teachers in order to take advantage of the opportunities that exist optimally.